Kecanggihan Teknologi Informasi, Kompetensi Sumber Daya Manusia dan Efektivitas Penggunaan Sistem Keuangan Desa - Premaswari, Ni Putu Sundari Maheni; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 31 No 8 (2021)DO - 10.24843/EJA.2021.v31.i08.p09, 2021)
The effective use of the village financial system can produce financial reports that are received in a timely, accurate, and reliable manner so that they can be used as a basis for decision making. The effectiveness of the use of the village financial system needs to be supported by the competence of good human resources and sophisticated information technology. This study aims to determine how the influence of information technology sophistication and human resource competence on the effectiveness of the use of the village financial system (Siskeudes) in the Village Government in Denpasar City. This research was conducted at the Village Government in Denpasar City with a saturated sampling technique using 54 samples. Data collection was carried out through interviews and questionnaires. The analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the more sophisticated the information technology and the better the competence of human resources, using the village financial system will be more effective. Keywords: Sophistication of information Technology; Human Resource Competence; Effectiveness of Using The Village Financial System.